2019
DOI: 10.1111/bph.14744
|View full text |Cite
|
Sign up to set email alerts
|

α7 nicotinic ACh receptors are necessary for memory recovery and neuroprotection promoted by attention training in amyloid‐β‐infused mice

Abstract: Background and Purpose Attention training reverses the neurodegeneration and memory loss promoted by infusion of amyloid‐β (Aβ) peptide in rats and increases the density of α7 nicotinic ACh receptors (α7nAChRs) in brain areas related to memory. Hence, we aimed to assess the role of α7nAChRs in the memory recovery promoted by attention training. Experimental Approach C57Bl/6 mice were chronically infused with Aβ, Aβ plus the α7 antagonist methyllycaconitine (MLA), or MLA alone. Control animals were infused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…In postsynaptic neurons, α7 nicotinic receptor activation induces the activity of CaMK-IV and transcription factors such as CREB. Recently our group showed that α7 nicotinic receptor blockade prevented memory retrieval in mice submitted to an experimental model of neurodegeneration (Telles-Longui et al, 2019). In the present work, SAMP-8 presented a significant decrease in the density of α7nAChR, when compared to SAMR-1, which may be related to the important memory loss observed.…”
Section: Effects On α7 Nicotinic Acetylcholine and Gabaa Receptorssupporting
confidence: 60%
“…In postsynaptic neurons, α7 nicotinic receptor activation induces the activity of CaMK-IV and transcription factors such as CREB. Recently our group showed that α7 nicotinic receptor blockade prevented memory retrieval in mice submitted to an experimental model of neurodegeneration (Telles-Longui et al, 2019). In the present work, SAMP-8 presented a significant decrease in the density of α7nAChR, when compared to SAMR-1, which may be related to the important memory loss observed.…”
Section: Effects On α7 Nicotinic Acetylcholine and Gabaa Receptorssupporting
confidence: 60%
“…The current results are consistent with previous reports on AD. A recent study found that cotreatment with MLA promoted the reduction of BDNF in the hippocampus and worsened Aβ-induced cognitive impairment, suggesting a determinant role of α7nAChR in BDNF expression and memory recovery in AD (Telles-Longui et al, 2019). Chen et al has also reported that α7nAChR blockade could inhibit the reverse of hippocampal BDNF and abolish the neuroprotective effects of simvastatin in Aβ 25-35 -mice, an inhibitor of 3-hydroxy-3-methyl-glytarylcoenzyme reductase, which is effective in improving cognition in AD patients (Wang et al, 2015).…”
Section: Regulation Of α7nachr On Bdnf Expression In the Hippocampusmentioning
confidence: 99%
“…In mammalian brain cells, the most commonly found nAChRs are the α4β2 heteromeric (α4β2-nAChR) and the α7 homomeric subunit–α7 nicotinic ACh receptor (α7-nAChR) [ 100 ], whose importance in AD treatment has been widely examined. For example, the stimulation of α7-nAChRs contributes to memory formation and consolidation [ 96 ] and cellular recovery after Aβ-induced neurotoxicity in mice [ 97 ]. On the other hand, the blockade of α7-nAChRs induces cognitive deficits in mice [ 98 ].…”
Section: Pi3k/akt Pathway Mediating the Multi-target Effects In Admentioning
confidence: 99%